An Ethnophysics E-Module Based on Indonesian Bamboo Spinning Tops for Contextual Mechanics Learning - Siti Muhafidhoh; Siti Wahyuni; Listiyanto Listiyanto; Hartono Hartono (Universitas Negeri Semarang, 2026)
This study aimed to analyze the characteristics of an integrated ethnophysics e-module for mechanics learning, determine its validity based on expert evaluations, and examine students’ responses toward its implementation. The study employed a Research and Development (R&D) method using the Four-D (4D) development model consisting of define, design, develop, and disseminate stages. The main characteristics of the developed e-module included integration of PDF and Google Sites, ethnophysics context and Magnus effect approach, multirepresentation mechanics materials, interactive multimedia features. The validation results showed that the developed e-module achieved an average percentage of 89.58% from material experts and 85.00% from media experts, both categorized as highly valid. In addition, the student response results obtained an average percentage of 90.25%, categorized as very positive. These findings indicate that the developed ethnophysics e-module has the potential to support contextual, interactive, and technology-based mechanics learning through the integration of local cultural phenomena and digital learning media.